2020
DOI: 10.1088/1361-6528/ab5e3e
|View full text |Cite
|
Sign up to set email alerts
|

Improved figures of merit of nano-Schottky diode by embedding and characterizing individual gold nanoparticles on n-Si substrates

Abstract: Improving Schottky diode characteristics in semiconducting devices is essential for better functionality in electronic and optoelectronic devices at nanoscale. In this paper, we investigate the electric transport characteristics of a gold (Au)-tip/n-Si-based nano-Schottky diode by using a conductive-mode atomic force microscope (CAFM). First, 10 nm average diameter Au nanoparticles (NPs) are monodispersed on the highly cleaned n-type Si substrate using an optimized spin-coating technique. The controlled and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“… 1 One of the novel techniques to realize nanoantennas at a nanoscale is to utilize nanoprobes (or ultrasharp tips) 2 4 that will be used to make physical contact with individual CNTs and form a nano-Schottky diode rectifier. 5 Additionally, we have demonstrated the feasibility of designing an optical rectenna by engineering a rectifying diode at the interface between a metal nanoprobe of an atomic force microscope (AFM) and single-wall carbon nanotubes (SWCNTs). 6 This has paved the way for more investigations, wherein, in this work, we study the effect of the metal type of the nanoprobe on the rectenna performance.…”
Section: Introductionmentioning
confidence: 99%
“… 1 One of the novel techniques to realize nanoantennas at a nanoscale is to utilize nanoprobes (or ultrasharp tips) 2 4 that will be used to make physical contact with individual CNTs and form a nano-Schottky diode rectifier. 5 Additionally, we have demonstrated the feasibility of designing an optical rectenna by engineering a rectifying diode at the interface between a metal nanoprobe of an atomic force microscope (AFM) and single-wall carbon nanotubes (SWCNTs). 6 This has paved the way for more investigations, wherein, in this work, we study the effect of the metal type of the nanoprobe on the rectenna performance.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this has been integrated with a new approach used for modeling and fabrication of a tunneling-based nano-Schottky diode rectier. 5 CNTs' outstanding electrical, mechanical, and physical properties make them ideal candidates for many potential applications including transistors, [6][7][8] gas sensors, 9,10 optical sensors, 11 light emitters 12,13 and for MEMS/NEMS applications. 14 Also, CNTs make exemplary antenna elements as they absorb electromagnetic energy in a broad spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] Namely, it has been reported that the photodetection and electrical characteristics depend only on the size of the metal-semiconductor nano interfaces. [10][11][12] Because of their compatibility with organic compounds and ability to bond with reduced graphene oxide the Au-NPs have been used to improve the efficiency of semiconducting devices. 13,14 The Au-NPs, being chemically stable with high work function, are considered to be excellent candidates for charge trapping elements.…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of these NPs on the substrate can be controlled by different deposition methods like spin coating and dip coating. 11,26,27 Recently, the solution processed Au-NPs have been used for electron storage centers by properly embedding NPs in the carefully engineered blocking and tunneling layers of Al 2 O 3 on an n-Si substrate. 26 To characterize individually or discretely dispersed NPs on the substrate, atomic force and scanning tunneling microscopies (AFM and STM) are considered to be among the best tools.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation